Pengaruh Keluarga, Pendidikan dan E-Commerce Pada Peningkatan Minat Wirausaha : Studi pada Mahasiswa Institut Bisnis dan Informatika Kosgoro 1957 - Muliyati Muliyati; Bambang Setyo Utomo (Prisani Cendekia, 2022)
This study aims to determine the effect of family, entrepreneurship education and e-commerce on entrepreneurial interest in IBI K1957 students. This research uses primary and secondary data. The sampling technique was carried out by purposive sampling as many as 50 respondents to IBI K 1957 students who had taken entrepreneurship courses. Based on data processing carried out with the SPSS 20 program, the coefficient of determination (adjusted r square) of 0.677 means that the contribution of family variables, entrepreneurship education and the use of e-commerce to the variable interest in entrepreneurship is 67.7% and the remaining 32.2% is influenced by other factors not included in this study. The results of the t-test, it was found that all variables had a significance value of less than 0.05, so that all variables partially affected the interest in entrepreneurship. The F test obtained a significant value of 0.000, meaning that family, entrepreneurship education and e-commerce simultaneously have a positive and significant effect on the entrepreneurial interest of IBI K1957 students